Competition between the rearrangement of electrodeposited overlayers of copper on platinum and the hydrogen electrode reactions - Margheritis, D. (1987)
The electrodeposition of Cu2+ ions on polycrystalline Pt from acid aqueous CuSO4, solutions was studied in the underpotential (upd) and overpotential (opd) ranges by using potentiostatic and potentiodynamic techniques. In the upd region, monotonic current transients were recorded for potentials (Ed) more positive than the reversible potential (Er) of the Cu2+/Cu electrode. For Cu electrodeposits involving a charge density close to that of the complete Cu monolayer, the hydrogen electrode reactions were strongly inhibited. Otherwise, non-monotonic current transients were recorded for Ed → Er. These transients suggest rearrangement of the monolayer structure when additional Cu atoms are deposited. In the opd region where the early stages of threodimensional(3D) nucleation and growth take place, the contribution of the hydrogen electrode reaction reappeared due to bare platinum sites which are present in the early stages of 3D growth. The present results in the limiting case can be interpreted in terms of a 2D to 3D transition at the overlayer level implying a certain distribution of clusters and the reappearance of the bare substrate surface. This process, in principle, accounts for the anomalies observed systematicly in vohammetric measurements for this system.